PENGARUH PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII DI SMP NEGERI 25 MAKASSAR - Rina, Aspah; Mustamin; Raehana, Syarifa; Wahab, Abdul; Subaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study employed a quantitative approach using an ex post facto research design. The population consisted of 150 students, and a sample of 60 students was determined using the Slovin formula with a 10% margin of error. The objectives of this study were to determine: (1) the implementation of the Teams Games Tournament (TGT) learning model, (2) students' learning motivation, and (3) the effect of the implementation of the Teams Games Tournament (TGT) learning model on students' learning motivation in Islamic Religious Education among eighth-grade students at SMP Negeri 25 Makassar. Data were collected through Likert-scale questionnaires and documentation, and were analyzed using descriptive and inferential statistical methods. Inferential analysis was conducted using the partial t-test and the coefficient of determination (R²) with the assistance of SPSS version 26.The results of the study indicate that: (1) the implementation of the Teams Games Tournament (TGT) learning model is categorized as moderate, with the percentage of class presentation at 78.33%, team formation at 51.67%, games tournament at 66.67%, and rewards at 58.33%; (2) students’ learning motivation is also categorized as moderate, with a frequency distribution of 15% in the low category, 65% in the moderate category, and 20% in the high category; and (3) there is a significant effect of the Teams Games Tournament (TGT) learning model on students’ learning motivation, as evidenced by the partial test (t-test) results in which all variables obtained significance values of less than 0.05. Furthermore, the coefficient of determination test shows an R Square value of 88,3%, indicating that the TGT learning model contributes 88.3% to students’ learning motivation, while the remaining 11.7% is influenced by other factors not examined in this study.